Clinical Case Report: Mondor's Disease - Temoche Espinoza, Edilberto (2020)
Mondor’s disease is a clinical entity characterized by the appearance of a palpable cord-like induration on the body's surface. In general it is considered as a self-limited benign thrombophlebitis that resolves in four or eight weeks without any specific treatment. A case of sudden onset and spontaneous favorable evolution is presented. A literature review on the subject is carried out.